Safety and Adverse Effects of Inactive SARS-Cov-2 Vaccine (CoronaVac) in Health Care Professionals - Guzel, Eda Celik; Yildiz, Tulin; Buyukkiyici, Onur; Dombaz, Oyku Elvin (Journal of the Pakistan Medical Association, 2022)
Objective: To assess adverse effects post-vaccination in healthcare professionals in the first vaccinated group against coronavirus disease-2019. Method: The prospective study was conducted at the vaccination unit of a university hospital in Tekirdag, Turkey, from January to February 2021, and comprised healthcare professionals who came for receiving the second dose of the coronavirus disease-2019 inactivated severe acute respiratory syndrome coronavirus 2 vaccine 28 days after the first dose. Data was analysed using SPSS 18. Results: Of the 1088 subjects, 714(65.6%) were female with mean age 29.85±9.2 years and 374(34.4%) were male with mean age 29.57±9.85 years. Overall, local pain in the vaccinated area 495(45.5%), fatigue 266(24.4%), headache 261(23.9%) and muscle pain 197(18.1%) were very common adverse effects. Conclusion: Inactivated severe acute respiratory syndrome coronavirus 2 vaccine was found to be safe. Key Words: CoronaVac, Post-vaccination adverse effects, Healthcare professionals.